Rule and perception based MAC protocol for UAN - Chong LI; Xiujuan DU; Lijuan WANG; Xiaojing TIAN (Tongxin xuebao)
Aiming at the problem of low channel utilization and network throughput resulted by RTS/CTS handshakes in the conventional media access control (MAC) protocol for underwater acoustic network (UAN), a rule and perception based (RP-MAC) MAC protocol was proposed to avoid packet collision in underwater acoustic networks.Only when the designated receiving node was neither in sending nor receiving state, and other neighboring nodes were not in receiving state, a sending node could send one or more packets to the receiving node, which avoided the interaction of handshake control packets while reducing collision and retransmission.The status of the neighbor nodes was sensed according to the channel rules and the fields from the packets overheard.Theoretical analysis and simulation experiments show that the performance of RP-MAC protocol outperforms the Slotted FAMA and R-MAC protocol in terms of throughput and energy-consumption.